Understanding Behavior of Household Food Waste Management: Food Waste Hierarchy Context - Luthfina Ariyani; Kirana Rukmayuninda Ririh (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2020)
The determinant factor identification of behavior considers as an important means in order to develop effective intevention towards household waste management in Indonesia. This study extended the Theory of Planned Behavior (TPB) by using the following construct: intention, attitude, subjective norm, perceive behavioral control, government intervention, environmental knowledge and awareness, as well as household planning and buying habit; to understand household waste management behavior from the ‘reduce-reuse-recycle’ point of view. The structural equation modeling (SEM) were used in this study and the result showed that the model accounted for relatively substantial amount (61.7%) of the variance in intention, with the attitude, subjective norm, and environmental knowledge and awareness emerge as significant predictor. Above findings could be used by both governmental and non-governmental organization to formulate strategies to manage food waste at the household level.